Digital signal transmission from fully implantable CMOS image sensor in simulated body environment. Issue 12 (1st June 2014) - Hayami, H.; Ishii, Y.; Sasagawa, K.; Noda, T.; Tokuda, T.; Ohta, J.
Abstract : A method for wireless data transmission from an implantable image sensor through the biological tissue as a conductive medium is reported. A battery‐powered implantable image sensor unit is dipped in phosphate‐buffered saline (PBS) as the simulant body solution and received the data signal through the PBS. Its equivalent circuit model for simulation is also proposed. The transmitted signal waveforms are in good agreement with the simulation result. Image recovery from the signal obtained from the implantable image sensor received outside the PBS is also demonstrated.